Psychological Distress Pada Orang Dengan Hiv/Aids (Odha) Ditinjau Dari Tingkat Resiliensi - Syafira Putri Ekayani; Riska Anggita Nawangsih; Ika Retno Priani (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: People living with HIV/AIDS (PLWHA) often face various forms of stigma while managing their illness, which makes them more vulnerable to psychological distress. However, some PLWHA demonstrate the ability to recover and adapt well, effectively managing their psychological condition—these individuals typically possess strong resilience. Objective: This study examines the relationship between resilience and psychological distress among PLWHA in Sorong City. Method: The study involved 99 male and female participants, recruited through a snowball sampling technique. Data were collected using the CD-RISC scale to measure resilience and the DASS-21 scale to assess psychological distress. A correlational quantitative method was employed, with Spearman’s rank-order correlation used for analysis. Result: The results revealed a significant correlation between resilience and psychological distress (p = 0.005; p < 0.05), with a correlation coefficient of -0.278. Conclusion: The study concludes that there is a negative relationship between resilience and psychological distress. In other words, the higher the resilience of PLWHA, the lower their likelihood of experiencing psychological distress